Borges and the logic of quantum physics - Arbaiza-Escalante, Luis Bertrand (2022)
The logic of quantum physics was related to two texts by the writer Jorge Luis Borges: Tlön Oqbar Orbis Tertius and La lotería en Babilonia. The topics were the following: The quantum world violates the principle of identity, Borges and Schrödinger agree that the concept of identity does not make sense for coins in Borges's story and for elementary particles for the physicist, since identity is different to indistinguishable, the logicians Da Costa and Krause outline a formalized theory for elements distinguishable as individuals but indistinguishable as a class: the quasi-set. The quantum world challenges predicate logic, because in quantum field theory there is no physical substance, an object is nothing more than a set of properties as in Tlön Ouqbar Orbis Tertius. The quantum world violates causal determination, everything is indeterminacy as in Lottery in Babylon. These examples, poetically prophesied by Borges make us doubt the universality of logic, it was proposed that logical intuition is a product of the evolution of the brain, it is innate and acquired its form depending on the world: logic is like that because the world it is so. Therefore, it is true but not universal.